2016
DOI: 10.1007/s00464-016-5053-0
|View full text |Cite
|
Sign up to set email alerts
|

The safety of laparoscopic sleeve gastrectomy among diabetic patients

Abstract: Laparoscopic sleeve gastrectomy is a safe procedure for type 2 diabetics with regard to early postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Similar to our findings, Steele et al demonstrated in their study on 22,288 bariatric cases an increased risk of cardiac, infectious, and renal complications in diabetic patients although patients were not stratified based on insulin requirement status [12]. Some studies have failed to demonstrate increased complications with LSG and LRYGB in diabetics [8,9]. Nevertheless, these studies were smaller and likely underpowered.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to our findings, Steele et al demonstrated in their study on 22,288 bariatric cases an increased risk of cardiac, infectious, and renal complications in diabetic patients although patients were not stratified based on insulin requirement status [12]. Some studies have failed to demonstrate increased complications with LSG and LRYGB in diabetics [8,9]. Nevertheless, these studies were smaller and likely underpowered.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, there may be some concerns about the safety of bariatric surgery in diabetic patients since DM has been associated with increased perioperative complications including anastomotic leak as well as mortality [6,7]. This does not seem to be a consistent finding as some studies have failed to demonstrate that increased risk [8,9]. Furthermore, there is paucity of literature on the differences in perioperative outcomes in diabetics who require insulin therapy compared with those who do not.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Creange et al[41] based on the American College of Surgeons-National Surgical Quality Improvement Program database of 2012, 941 out of 6062 LSG patients had T2DM (15.5%). As in our study, the T2DM patient group was more likely to be male and older.…”
Section: Discussionmentioning
confidence: 99%
“…In this analysis, type 1 and type 2 diabetes was found as a significant risk factor for 30 d complications. Creange et al[41] state that this difference in results stems from the contribution of type 1 diabetes patients in the Aminian et al[42] report. In our population, all patients with diabetes were diagnosed with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a potential risk factor for leaks, mostly in the super-obese population (BMI > 50 kg/m 2 ). 9,54,113 Diabetes is also linked to higher rates of leak after gastrointestinal surgeries in some studies, [114][115][116] but other studies failed to show an association. 129 Sleep apnea and male gender were associated with higher leak rates in one study.…”
Section: Nonsurgical Risk Factorsmentioning
confidence: 99%